MSMEs and Islamic Securities Crowdfunding: The Importance of Financial Literacy - Majid, Rifaldi; Nugraha, Rizky Aditya (Universitas Islam Internasional Indonesia, 2022)
The development of Islamic securities crowdfunding (I-SCF) financial technology has recently become a momentum for micro, small, and medium enterprises (MSMEs) in terms of fulfilling capital by issuing shares (sukuk) based on syariah principles. This research examines the role of Islamic financial literacy through the use of variables from the theory of planned behavior about the intentions of MSME actors to apply for capital through I-SCF. A total of 97 responses were collected from MSMEs owners/managers who have been in business for at least two years using an online questionnaire and then examined using structural equation modeling by SmartPLS. The results show that the variables of subjective norm, perceived behavioral control, and attitude toward behavior significantly influence the intention to obtain capital to expand one’s business. The primary finding of this research is that Islamic financial literacy has been experimentally shown to improve the desire of MSME players to expand their business capacity. There is thereby a need for continuous efforts from the Indonesian Financial Service Authority to collaborate with industry players, organising associations, and syariah scholars to boost Islamic financial literacy through sustainable education. In addition, efforts to maintain the uniqueness of I-SCF and its syariah compliancy must be supported by prospective I-SCF providers, even while awaiting their operational permits.